Identification of The Driving Factors Behind The Transformation of The Landscape in Sabang, Aceh, Indonesia, Based on Local Perception - Azwar, Faisal; Achmad, Ashfa; Mahidin, Mahidin; Irwansyah, Mirza (Elkawnie, 2025)
Abstract: Information on land use changes and land cover change studies to understand the dynamics of landscape change is very useful for planning sustainable landscape management. Changes to the landscape not only have an impact on people's welfare but also on the way people view and use the landscape. Land-based investments have implications for spatial development and influence landscape dynamics. Cities continue to experience growth, including cities on small islands. The city of Sabang, whose territory is small islands in Aceh Province, Indonesia, is experiencing an increase in local population, immigration, and government policy encouragement to improve the economy. It is worth paying attention to knowing the dynamics of landscape change and the driving factors based on local perceptions.  It is important to understand the patterns of land use and land cover changes from 2013 to 2021, as well as the driving factors based on local community perceptions that may influence future spatial planning and land utilization in Sabang City.  This study uses mixed methods consisting of analysis of land use and land cover change patterns based on remote sensing using ArcGIS and TerrSet software on Spot 6 and Spot 7 image data to provide information on the transition of land cover change. The results of the analysis of changes in land use and land cover from 2013 to 2021 and the driving factors based on local perceptions from elements of Sabang City society were carried out through questionnaires and semi-structured interviews covering 120 households. To assess the drivers of changes in the Land Use and Land Cover (LUCL) of the Sabang City area, which were analyzed using the Statistical Package for Social Sciences (SPSS) for Windows. The results of the analysis of changes in land use and land cover show that most of the land in Sabang is still covered by forest land in 2021, namely 50%. 175 ha, or 67%, of the growing built-up area is covered, while the infilling and outlying patterns are 44 ha and 42 ha, respectively. Respondents identified 17 driving factors, namely 10 proximate driving factors and 7 fundamental driving factors, as important drivers that contribute to changes in the landscape of Sabang City. The three closest drivers are Residential Areas, Forest Fires and Infrastructure Development. Meanwhile, land needs, changes in land prices and population growth are the three main drivers of LULC changes in Sabang City. Abstrak: Informasi perubahan penggunaan lahan dan studi perubahan tutupan lahan untuk memahami dinamika perubahan lanskap sangat berguna untuk perencanaan pengelolaan lanskap yang berkelanjutan. Perubahan pada lanskap tidak hanya berdampak pada kesejahteraan masyarakat namun juga cara masyarakat memandang dan memanfaatkan lanskap. Investasi berbasis lahan berimplikasi pada pembangunan ruang dan mempengaruhi dinamika lanskap. Kota-kota terus mengalami pertumbuhan, termasuk kota di pulau kecil. Kota Sabang yang wilayahnya merupakan pulau-pulau kecil di Provinsi Aceh, Indonesia mengalami peningkatan populasi masyarakat lokal, imigrasi serta dorongan kebijakan pemerintah dalam meningkatkan perekonomian, patut menjadi perhatian untuk mengetahui dinamika perubahan lanskap serta faktor pendorongnya berdasarkan persepsi lokal. Bagaimana pola penggunaan lahan dan tutupan lahan yang terjadi dalam waktu tahun 2013-2021, dan bagaimana persepsi masyarakat lokal dalam melihat faktor pendorong perubahan penggunaan lahan dan tutupan lahan di Kota Sabang.  Studi ini menggunakan metode campuran yang terdiri dari analisis pola perubahan penggunaan lahan dan tutupan lahan berbasis penginderaan jauh menggunakan software ArcGIS dan TerrSet terhadap data Citra Spot 6 dan Spot 7 yang memberikan informasi transisi perubahan tutupan lahan.  Hasil analisis perubahan penggunaan lahan dan tutupan lahan 2013-2021, kemudian faktor pendorongnya berdasarkan persepsi lokal dari unsur masyarakat Kota Sabang dilakukan melalui kuesioner dan wawancara semi-terstruktur yang mencakup 120 rumah tangga. Untuk menilai pendorong perubahan penggunaan lahan dan tutupan lahan wilayah Kota Sabang yang dianalisis menggunakan Statistical Package for Social Sciences (SPSS) untuk Windows. Hasil analisis perubahan penggunaan lahan dan tutupan lahan menunjukkan sebagian besar lahan di Sabang masih ditutupi oleh lahan hutan pada tahun 2021 yaitu sebesar 50%, telah turun luasnya sekitar 7% dibanding tahun 2013. Lahan terbangun di Kota Sabang sebagian besar tumbuh dengan pola perluasan/ekspansi seluas 175 ha atau mencakup 67% dari luas area terbangun yang bertumbuh, sedangkan pola infilling dan outlying masing-masing seluas 44 ha dan 42 ha. Responden mengidentifikasi 17 faktor pendorong, yaitu 10 faktor pendorong terdekat dan 7 faktor pendorong mendasar sebagai pendorong penting yang berkontribusi terhadap perubahan lanskap Kota Sabang. Tiga besar pendorong terdekat adalah kawasan permukiman, kebakaran hutan dan pembangunan infrastruktur. Sedangkan Kebutuhan Lahan, Perubahan harga lahan dan Pertumbuhan penduduk merupakan tiga besar pendorong mendasar perubahan LULC di Kota Sabang